2016
DOI: 10.1111/1477-8947.12089
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and wetland conservation: application of travel cost and willingness to pay an entry fee at Ghodaghodi Lake Complex, Nepal

Abstract: This study investigated the need and applicability of wetland tourism for resource conservation, using the case of Ghodaghodi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…By using travel cost method, the value of the recreational site are to be inferred by collecting and processing the travel costs that the people have to pay to visit that site (Bockstael, 1995). Travel costs consist of transportation expenses, entering fee to the recreation area and costs of travelling time, therefore the term "travel costs" refers to the total cost of a visit or trip (Lamsal et. al, 2016;Zhang et.…”
Section: Revealed Preference Methodsmentioning
confidence: 99%
“…By using travel cost method, the value of the recreational site are to be inferred by collecting and processing the travel costs that the people have to pay to visit that site (Bockstael, 1995). Travel costs consist of transportation expenses, entering fee to the recreation area and costs of travelling time, therefore the term "travel costs" refers to the total cost of a visit or trip (Lamsal et. al, 2016;Zhang et.…”
Section: Revealed Preference Methodsmentioning
confidence: 99%
“…They are important for policy makers to understand the values of biodiversity at species, community and ecosystem levels in national economies. Research in Nepal has ranged from using contingent valuation [85] to assess the value of vultures [68,69], using travel cost methods to explore the values of wetlands [86], to assessing possibilities for, and economics of, implementing REDD (reducing emissions from deforestation and degradation, [87]). Various findings have shown that fees foreign tourists are willing to pay for entry permits into PAs are frequently higher than what governments charge (e.g.…”
Section: More Recently…mentioning
confidence: 99%
“…Thus, in this paper, we seek to explore whether these two methods give consistent results when assessing the ecosystem services values of the same wetland. This research contributes to identifying a more accurate and efficient scale transform method for wetland evaluation at a larger space-scale, providing a technique tool for establishing wetland ecological compensation systems at different spatial patterns, conducting large-scale wetland protection projects, and accounting for green GDP [28][29][30][31]. The high-precision model can also be used in evaluating the ecological services of cross-regional, national and even international wetlands in further application.…”
Section: Introductionmentioning
confidence: 99%